Pengaruh Penggunaan Informasi Akuntansi terhadap Keberhasilan Usaha Mikro Kecil - Triyana Hasibuan, Henny (E-Jurnal Akuntansi; Vol 30 No 7 (2020), 2020)
Accounting information is a financial record that can be used by MSEs (Micro Small Business) to find out how much revenue should be received, how much operating costs should be incurred and how much profit or loss is obtained. The purpose of this study is to look at the effect of accounting information on the success of MSE businesses. The population of the study was MSEs  Tempe Chips Industry Center in Malang City. The sampling method used in the study used a formula so that the total sample was 60 MSEs actors. The results showed that the use of accounting information significantly influenced the success of MSEs in the Sanan Malang City tempe chips industry center. Limitations This study only focuses on the variable use of information on business success. In addition, subjective respondents 'answers, this is due to respondents' answers leading to the perception of respondents in using accounting information for business success. Keywords: Use of Accounting Information; Micro Small Business (MSEs); Business Success.